Financing clean energy in developing Asia - Susantono,Bambang; Zhai, Yongping; Shrestha,Ram; Mo, Lingshui (Manila Asian Development Bank, 2021)
It reviews existing financing options and approaches for clean energy, and includes country examples of how these have been applied. Innovative solutions for mobilizing private finance and managing risks associated with clean energy investments are also discussed. The book is the first of two volumes that look at various approaches and instruments that have been tried, tested, and utilized to scale up clean energy development in the region.
Keywords: Clean energy investment -- Asia; Clean energy industries -- Asia; Electronic books